Development of an improved camping fire pit / Siti Amirah Ahmad Shaharul Bahrim - Ahmad Shaharul Bahrim, Siti Amirah (2024)
The camping fire pit was an important piece of equipment for camping activity, especially at night because the main usage was to light a fire that could warm the body. However, there were lots of campers who burned their fuel, such as charcoal and wood, on the ground, which caused harm to the environment. Hence, this study was designed to create a portable and foldable camping fire pit that could be packed and transported easily using a mechanical engineering design process. The modeling for this product was developed using SolidWorks software. In addition, this product was specially designed with a suitable shape, was easy to install, and hence could be carried anywhere. This fire pit also had a feature with a container that could retain the fuel used. At the end of the study, this product presented a convenient and useful functionality that helped users with camping activities. At the same time, it was also environmentally friendly.